Sex-Based Differences in the Incidence of Sports-Related Concussion: Systematic Review and Meta-analysis. (November 2019) - Cheng, Jennifer; Ammerman, Brittany; Santiago, Kristen; Jivanelli, Bridget; Lin, Emerald; Casey, Ellen; Ling, Daphne
Context: The incidence of sports-related concussion in females has been increasing in recent years. Objective: To conduct a meta-analysis on sex-based differences in concussion incidence in various sports and to determine the effects of study design (retrospective vs prospective), setting (competition vs practice), and population (university and above vs high school and below) via a meta-regression. Data Sources: PubMed (Medline), EMBASE, and Cochrane Library databases were searched from January 2000 to January 2018. Study Selection: Studies reporting sports-related concussion incidence data for both males and females (age ≥10 years) were included. Study Design: Systematic review with meta-analysis and meta-regression. Level of Evidence: Level 4. Methods: The rate ratio was calculated as the concussion rate in females/males. Data were pooled using the DerSimonian-Laird random-effects model. Results: Thirty-eight studies met the eligibility criteria and were included in the meta-analysis. Soccer and basketball demonstrated significantly higher incidence of concussions in females compared with males (rate ratio [95% CI], 1.76 [1.43-2.16] and 1.99 [1.56-2.54], respectively; P < 0.01). Sex-based differences in concussion incidence rates for baseball/softball, ice hockey, lacrosse, swimming/diving, and track and field were not statistically significant. In the meta-regression analysis, there were no significant effects on the rate ratio when evaluating study design, setting, and population. Conclusion: Concussion incidence rates were significantly higher in females than in males for soccer and basketball.